Metode TOPSIS Untuk Penerima Bantuan Pendidikan Bagi Mustahik Fakir - Devit Satria; Desyanti Desyanti; John Suarlin (Universitas Budi Darma, 2023)
Education is mandatory for all levels of society, every parent wants their children to be able to go to school properly, but the roots of education problems generally lie in financing for parents who have relatively low incomes. If conditions like this continue, Indonesia will lose the best generation if there are still many children who do not go to school due to the cost factor. The Dumai City National Amil Zakat Agency (BAZNAS) is one of the Amil Zakat Agencies in Riau Province. The Dumai City Baznas created an educational assistance program for poor families in the form of money to buy school supplies. Mustahik who wish to receive educational assistance must fill out a form and other predetermined conditions. After that, Baznas will select the incoming proposals and carry out the selection process. The large number of proposals caused Baznas to take a long time to make a decision because they had to check the submitted documents one by one, because it took a long time, the proposal for submitting assistance was approved based on the results of the meeting and agreement with the chairman of BAZNAS. So that the results decided are not as optimal as the actual conditions. For this reason, a system is needed that can assist BAZNAS in carrying out the document selection process in accordance with the requirements so that the assistance provided is right on target and can determine priorities for recipients of educational assistance for mustahik. The TOPSIS method is able to provide solutions to problems that occur, from the results of research conducted by Sutjiati Gita Lestari, it is ranked 1st with a value of 0.8041